2021
DOI: 10.1108/jarhe-10-2020-0378
|View full text |Cite
|
Sign up to set email alerts
|

From Industry 4.0 to Education 4.0: acceptance and use of videoconferencing applications in higher education of Oman

Abstract: PurposeThe present paper is an attempt to study Education 4.0 supported by Industry 4.0 tools and techniques. The main purpose of the study is to examine the acceptance and use of one of the internet of things (IoT)-based learning management systems, i.e. videoconferencing application (Google Meet, Microsoft Teams, Zoom, GoToMeeting, WebEx), by academicians of higher education using the unified theory of acceptance and use of technology (UTAUT) model.Design/methodology/approachThe study comprises 218 responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 82 publications
2
13
0
Order By: Relevance
“…Many scientists have found that people who own vehicles have a good understanding of the effects of these vehicles on the environment and a better understanding of how to maintain and treat end-of-life vehicles (Ukonze et al, 2020;Yang et al, 2022). Age was also found to have a significant influence on respondents' knowledge of ELV-related knowledge, which is consistent with previous studies in which gender was found to be a determining factor in a person's high and low knowledge of government regulations (Shallcross et al, 2013;Vaghee et al, 2017;Yang & Shih, 2020;Jain & Jain, 2022). One very interesting finding in the results of this study is: that gender is a predictor that significantly affects a person's knowledge.…”
Section: Discussionsupporting
confidence: 84%
“…Many scientists have found that people who own vehicles have a good understanding of the effects of these vehicles on the environment and a better understanding of how to maintain and treat end-of-life vehicles (Ukonze et al, 2020;Yang et al, 2022). Age was also found to have a significant influence on respondents' knowledge of ELV-related knowledge, which is consistent with previous studies in which gender was found to be a determining factor in a person's high and low knowledge of government regulations (Shallcross et al, 2013;Vaghee et al, 2017;Yang & Shih, 2020;Jain & Jain, 2022). One very interesting finding in the results of this study is: that gender is a predictor that significantly affects a person's knowledge.…”
Section: Discussionsupporting
confidence: 84%
“…These agree that, in addition to providing students with increased capabilities, the use of project-based learning considering the STEAM (Science, Technology, Engineering, Arts, and Mathematics) fields and I4.0 also help teachers obtain greater knowledge about the area which is presented as fundamental. Even during the COVID-19 pandemic, some authors understood that the I4.0 concepts are so crucial that they created online materials to teach these subjects, as mentioned by Benis et al (2021) , Jain and Jain (2021) and Jena et al (2022) .…”
Section: Related Workmentioning
confidence: 99%
“…The principal platforms of online learning that allow live interaction between teachers and students are Zoom, Google Meet, Microsoft Teams, and recently, the use of group videoconferencing on WhatsApp. These apps have demonstrated their efficiency in working with different academic content in universities, high schools, and primary schools [3].…”
Section: -Introductionmentioning
confidence: 99%